Sleeping quality evaluation in patients with breast cancer in chemotherapy - Amorim, Jefferson Rodrigues; Silva, Igor Almeida; Shimizu, Iara Sayuri (Revista Brasileira de Mastologia, 2017)
Introduction: Chemotherapy is more used for retardation and control of breast neoplasms. However, patients undergoing chemotherapy often have to deal with numerous complications during treat-ment, which can affect the quality of sleeping. Objectives: To evaluate the sleeping quality of patients with breast cancer undergoing chemotherapy and to compare groups with good (G1) and poor (G2) quality of sleeping. Methods: Observational, quantitative and cross-sectional study with 36-patient sample. It was collected body mass index (BMI), cancer staging and it was applied the PSQI- Br, EORTC-C30, revised Piper Scale, ESS-Br, Insomnia Severity Index, Visual Analog Scale. We used the Pearson correlation test to associate the variables between themselves as well as the t test and χ2 test for comparison purposes between groups G1 and G2. Results: The PSQI- Br of the sample analyzed was 5.36±2.73. Out of 36 participants, 21 (58.4%) had poor sleep getting a score of 5 to 10. As for the other 15 patients (41.8%) had a score of 0 to 4, showing a good sleeping quality. Conclusion:The levels of PSQI-Br exposed a poor quality of sleeping in patients with breast cancer chemotherapy as well as significant difference between the groups G1 and G2 in the variables age, BMI, pain, fatigue, quality of sleeping and life.